Enhancing Water Productivity and Flower Yield of Tuberose through Drip Fertigation and Optimized Land Configurations in Semi-Arid Region - Badrigari Soujanya; Dhara Singh Gurjar; Pothula Srinivasa Brahmanand; Ajai Kumar Tiwari; Samrath Lal Meena; Shiv Prasad; Basaraveni Gouthami; Aditya Machnoor; Naveen Kumar (BioResources)
The economic and agronomic impacts of drip fertigation techniques were evaluated on tuberose (Polianthes tuberosa L.) cultivation in a semi-arid region. Conducted over two growing seasons (2022-2024) at the ICAR-Indian Agricultural Research Institute in New Delhi, the field experiments utilized a split-split plot design with three factors: land configuration (raised bed and flatbed), irrigation schedules (50%, 75%, and 100% pan evaporation), and fertigation schedules (50%, 75%, and 100% recommended dose of fertilizers). Data were collected on flower yield, water productivity, and economic returns. The raised bed system consistently outperformed the flat bed system in water productivity and flower yield. Among the irrigation levels, the highest water productivity and flower yield were observed at 100% pan evaporation. Similarly, the highest fertigation level (100% RDF) resulted in the best outcomes in terms of both yield and economic returns. The economic analysis revealed that the raised bed configuration with higher fertigation and irrigation levels (BI3F3) was the most profitable, with the highest benefit-cost ratios. The study concludes that optimizing fertigation and irrigation practices, particularly using raised bed configurations with higher fertigation and irrigation levels, can significantly enhance tuberose cultivation’s profitability and sustainability in water-scarce regions.